Opportunities for Shared Decision Making in Kidney Transplantation. Issue 5 (14th March 2013) - Gordon, E. J.; Butt, Z.; Jensen, S. E.; Lok‐Ming Lehr, A.; Franklin, J.; Becker, Y.; Sherman, L.; Chon, W. J.; Beauvais, N.; Hanneman, J.; Penrod, D.; Ison, M. G.; et al.
<x xml:space="preserve">Abstract</x> Health researchers and policy‐makers increasingly urge both patient and clinician engagement in shared decision making (SDM) to promote patient‐centered care. Although SDM has been examined in numerous clinical settings, it has received little attention in solid organ transplantation. This paper describes the application of SDM to the kidney transplantation context. Several distinctive features of kidney transplantation present challenges to SDM including fragmented patient–provider relationships, the time‐sensitive and unpredictable nature of deceased organ offers, decision‐making processes by transplant providers serving as both organ guardians (given the organ scarcity) versus advocates for specific patients seeking transplantation, variable clinical practices and policies among transplant centers, and patients' potentially compromised cognitive status and literacy levels. We describe potential barriers to and opportunities for SDM, and posit that SDM is feasible, warranting encouragement in kidney transplantation. We propose strategies to promote and overcome obstacles to SDM in kidney transplantation. We contend that engagement in SDM can be facilitated by re‐organization of clinical care, communication and education of providers and patients.